Letter from Margaret M. Booth to R.E. Preston - Martinez Cardeza, Margaret (1890)
Margaret M. Booth née Cardeza writes to Robert E. Preston (1836-1911) requesting he contacts the attorney Henry M. Baker on her behalf.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Preston, Robert E., 1836–1911; United States Mint; Mint of the United States